Answer:
20
Step-by-step explanation:
Cause im smart and you should trust me. duh
Distribute the 1/4:
1/4(16x) + 1/4(20) - 7x
Do the multiplication:
1/4(16x) = 16x/4 = 4x
1/4 (20) = 20/4 = 5
Now you have:
4x + 5 - 7x = 0
Combine like terms (4x and -7x):
-3x + 5 = 0
Subtract 5 from both sides:
-3x = -5
Divide by -3:
x = -5/-3 = 5/3
Answer:
x= 5/3
Answer:
The answer is C=6p3 + 29p2 + 22p – 21
Step-by-step explanation:
To calculate the product, we need to multiply each member of each multiplier:
(2p + 7)(3p2 + 4p – 3) = 2p · 3p² + 2p · 4p + 2p · -3 + 7 ·3p² + 7 · 4p + 7 · -3
= 6p³ + 8p² - 6p + 21p² + 28p - 21
= 6p³ + 8p² + 21p² + 28p - 6p -21
= 6p³ + 29p² + 22p - 21
Therefore, the product of (2p + 7)(3p2 + 4p – 3) is 6p³ + 29p² + 22p -21
Answer:
x=7, x= -2
Step-by-step explanation:
- Start by putting the whole equation to one side: x2-5x=14 ----> x2-5x-14=0
- Next, factor the equation: x,x -7,2 ----> (x-7)(x+2)=0
- Now, solve both equations: x-7=0....x=7 AND x+2=0.....x= -2
- Plug both in to make sure that they are correct....both are correct
Answer:
x^3+3x^2+4x+5
Step-by-step explanation:
Ok, so what helps me solve this kind of problem is to circle, underline, or box the like terms(the ones with the same exponent and variable). Be sure to note the sign of each term when combining like terms. take it one step at a time, and work downwards starting with the highest exponent. You have -x^3 and +2x^3, which is x^3. Next, you have +2x^2 and +x^2, which is 3x^2. You should write down each of these as you go, so you should now have x^3+3x^2. Then combine the terms with no exponent but with x, which is 5x and -1x, which is +4x. You should have x^3+3x^2+4x now. Lastly, just combine the numbers 1, -1, and 5, which is 5. This gives you an answer of x^3+3x^2+4x+5.